Use of History Teaching Materials for Specialization and Appreciation of SMA/MA Students in Brebes Regency - Safitri, Sindi; Atmaja, Hamdan Tri (Universitas Negeri Semarang, 2022)
This study aims to know the use of historical specialization teaching materials in early world civilization materials by history teachers in third graders High Schools/Madrasah Aliyah of the same level in Brebes and then to know student appreciation towards the history book used in historical subjects and implementation of teaching history material in learning history. The type of this research was qualitative, with data collection techniques using direct observation, in-depth interviews, and document studies. The results of this study indicate that the use of teaching materials provided by the schools has not been optimal. However, teachers use varied teaching materials that can increase student learning motivation. Student appreciation of valuing and assessing textbooks shows uniformity, but in the aspect of appreciating/interpreting students from two schools that are MAN 2 Brebes and SMAN 1 Bantarkawung, known that a small number does not have supporting books that are worksheets and summary of material prepared by teacher indicates that students have not appreciated/interpreted as an essential element in learning history. Teachers implement teaching materials by integrating teaching materials into learning methods that are interesting and varied. However, two of the three schools have technical problems in using instructional media; these were the availability of LCDs and inadequate projectors.